GEODYNAMICS AND METALLOGENY OF THE KEIVY DOMAIN (BALTIC SHIELD) - Kozlov N.E.; Sorokhtin N.O.; Martynov E.V.; Marchuk T.S. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Мурманский государственный технический университет», 2020)
Received in revised 20.02.2020 Geodynamic and petrogeochemical study of the Keivy domain in the Baltic Shield has shown that it was overlapped by surrounding microcontinents in the Archean. As a result, the Baltic Shield was subject to cratonization. Thus, the Keivy microcontinent can be considered as the most ancient known median massif of the continental crust. Specific features of its geodynamic evolution predetermined conditions for formation of unique in scale stratiform deposits of alumina raw materials on the surface of the microcontinent. The paper describes and justifies the mechanism of alumina formation by physical-chemical decomposition of Archean and early Proterozoic metamorphosed sedimentary complexes in the Kola region of the Baltic Shield. Besides, the study of metallogenic features of transformation processes in the Archean continental crust of the Keivy microcontinent and its rimming suggests that carbonaceous schists of the Keivy domain that formed in the sedimentary cover can be significantly rich in nanogold. It will allow considering the central part of the Kola region as a major gold-bearing province. The authors believe that the metallogenic forecast based on geodynamic reconstructions is promising for further research of early Precambrian complexes. This work continues a series of publications on structural-material study of the Keivy domain.
Keywords: РАННИЙ ДОКЕМБРИЙ; НЕОАРХЕЙ; СУПРАКРУСТАЛЬНЫЕ ПОРОДЫ; ГЕОДИНАМИЧЕСКАЯ ЭВОЛЮЦИЯ; МЕТАЛЛОГЕНИЯ; НАНОЗОЛОТО; ГЛИНОЗЕМИСТОЕ СЫРЬЕ; СРЕДИННЫЙ МАССИВ; EARLY PRECAMBRIAN; NEOARCHEAN; SUPRACRUSTAL ROCKS; GEODYNAMIC EVOLUTION; METALLOGENY; NANOGOLD; ALUMINA RAW MATERIALS; MEDIAN MASSIF; 551+552.4 (234.74); Precambrian::Archean::Neoarchean; Докембрий::Архей::Неоархейская